Recent Advances in Optical Biosensors for Environmental Monitoring and Early Warning - Anna Zhu; Feng Long; Hanchang Shi (Sensors, 2013)
The growing number of pollutants requires the development of innovative analytical devices that are precise, sensitive, specific, rapid, and easy-to-use to meet the increasing demand for legislative actions on environmental pollution control and early warning. Optical biosensors, as a powerful alternative to conventional analytical techniques, enable the highly sensitive, real-time, and high-frequency monitoring of pollutants without extensive sample preparation. This article reviews important advances in functional biorecognition materials (e.g., enzymes, aptamers, DNAzymes, antibodies and whole cells) that facilitate the increasing application of optical biosensors. This work further examines the significant improvements in optical biosensor instrumentation and their environmental applications. Innovative developments of optical biosensors for environmental pollution control and early warning are also discussed.